2018
DOI: 10.1519/jsc.0000000000002428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric and Resistance Training on Muscle Strength, Explosiveness, and Neuromuscular Function in Young Adolescent Soccer Players

Abstract: This study examined the effect of 8-weeks of free-weight-resistance (RT) and plyometric (PLYO) training on maximal strength, explosiveness and jump performance compared with no added training (CON), in young male soccer players. Forty-one 11[FIGURE DASH]13-year-old soccer players were divided into three groups (RT, PLYO, CON). All participants completed isometric and dynamic (240°/s) knee extensions pre- and post-training. Peak torque (pT), peak rate of torque development (pRTD), electromechanical-delay (EMD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 41 publications
4
63
0
13
Order By: Relevance
“…As for the quadriceps muscle, few authors (Pottiger Jeffrey et al, 1999;Malisoux et al, 2006a,b) reported hypertrophy of both slow and fast fibers of the VL following 8 weeks of intervention. McKinlay et al (2012) reported an 8.1% increased VL muscle thickness after 8 weeks of PLT, and Váczi et al (2014) found a 2.5% increase in quadriceps CSA measured via magnetic resonance after 10 weeks of intervention in elderly people. Very interestingly, Earp et al (2015) trained for 8 weeks 18 subjects with squat jumps (9 with parallel thigh depth jumps and 9 with volitional depth jumps), and found increases in QF and VL CSA in the distal (33%) and mid (50%) sites of the muscles.…”
Section: Adaptations In Muscle Sizementioning
confidence: 99%
“…As for the quadriceps muscle, few authors (Pottiger Jeffrey et al, 1999;Malisoux et al, 2006a,b) reported hypertrophy of both slow and fast fibers of the VL following 8 weeks of intervention. McKinlay et al (2012) reported an 8.1% increased VL muscle thickness after 8 weeks of PLT, and Váczi et al (2014) found a 2.5% increase in quadriceps CSA measured via magnetic resonance after 10 weeks of intervention in elderly people. Very interestingly, Earp et al (2015) trained for 8 weeks 18 subjects with squat jumps (9 with parallel thigh depth jumps and 9 with volitional depth jumps), and found increases in QF and VL CSA in the distal (33%) and mid (50%) sites of the muscles.…”
Section: Adaptations In Muscle Sizementioning
confidence: 99%
“…The long jump performance increase during the simulation competition when the oligomeric conditioning exercise is carried out 3 minutes before each experiment. This improvement is attributed to the progressive increase in the vertical speed of takeoff, while there is no effect on horizontal speed (Bodanis, G. C., Tsokkos, A., & valgus, a. a.; Whitehead, Schett, Michigan, & Martin, 2018;McKinlay et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To increase the efficiency of the trainings, it is stated that the exercises involving large muscle groups should be performed first (1,3,12). It is possible to reach different results in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was recommended that the exercise order should be performed from multiple joint exercises to single joint exercises (1). Similarly, it was stated that the exercises involving large muscle groups at the beginning of the training and later the exercises involving small muscle groups should be performed to increase performance (1,3,12).…”
Section: Introductionmentioning
confidence: 99%